2006
DOI: 10.2165/00044011-200626110-00002
|View full text |Cite
|
Sign up to set email alerts
|

Health-Economic Comparison of Paricalcitol, Calcitriol and Alfacalcidol for the Treatment of Secondary Hyperparathyroidism during Haemodialysis

Abstract: This study evaluated the health-economic consequences of use of intravenous paricalcitol (Zemplar), oral calcitriol or oral and intravenous alfacalcidol for the treatment of patients with secondary hyperparathyroidism, focusing on a third-party payer perspective through inclusion of medication and hospital costs, survival rates and utilities. Cost values were based on German treatment recommendations and prices. Reference values for survival rates and utilities were based on the results of a MEDLINE search. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Similar trends are reported by the United Renal Data System between 1999 and 2008, with a declined use of intravenous calcitriol from 83.9% to 1.8%, accompanied by a raise in paricalcitol and doxercalciferol intravenous adoption [91]. Health-economic analysis observed that paricalcitol may have potential economic benefits in both CKD and dialysis patients compared to calcitriol and alfacalcidol [92, 93]. Furthermore, a recent economic analysis of the FARO survey observed that intravenous paricalcitol was more cost-effetctive compared to the combination of paricalcitol plus cinacalcet [94].…”
Section: Vdra: a Multifaceted Choice From Secondary Hyperparathyrosupporting
confidence: 54%
“…Similar trends are reported by the United Renal Data System between 1999 and 2008, with a declined use of intravenous calcitriol from 83.9% to 1.8%, accompanied by a raise in paricalcitol and doxercalciferol intravenous adoption [91]. Health-economic analysis observed that paricalcitol may have potential economic benefits in both CKD and dialysis patients compared to calcitriol and alfacalcidol [92, 93]. Furthermore, a recent economic analysis of the FARO survey observed that intravenous paricalcitol was more cost-effetctive compared to the combination of paricalcitol plus cinacalcet [94].…”
Section: Vdra: a Multifaceted Choice From Secondary Hyperparathyrosupporting
confidence: 54%
“…Our study demonstrates the economic burden of SHPT in diabetic predialysis CKD patients and the negative impact on disease progression. Previous studies have shown the economic advantage and improvement in survival of selective VDRA therapy in CKD stage 5 hemodialysis patients [14,15,16,17,18]. Further analyses are needed to assess whether early treatment with a selective VDRA in diabetic predialysis CKD patients can reduce such excessively high costs and positively impact the disease progression and clinical outcomes including survival.…”
Section: Discussionmentioning
confidence: 99%
“…71 This may be one of the reasons why a cost analysis suggested that the use of paricalcitol provided cost-savings compared with calcitriol, in spite of its higher price. 72,73 Limitations inherent of observational data apply to these studies as well, and short of an RCT their results can also be only viewed as hypothesis-generating.…”
Section: Which Vitamin D Analog Is the Best?mentioning
confidence: 99%